Organizational Culture, Compensation, and Career Development on Nurse Performance with Job Satisfaction as Intervening Variables - Ni Luh Darmayanti (Universitas Muhammadiyah Yogyakarta, 2019)
The purpose of this study is to determine the influence of organizational culture, compensation and career development of the nurses' performance through job satisfaction. This study uses a quantitative approach with cross-sectional survey method. The technique for collecting data in this study was a questionnaire measuring devices in the form of Agree-Disagree Scale, in which respondents are all nurses at X Hospital Denpasar many as 143 people. In this study, data analysis is performed using SEM assisted by AMOS 22 program. The results of this study indicated that organizational culture, compensation, and career development have a positive and significant impact on job satisfaction and nurses performance at X Hospital Denpasar. In addition, the results of this study also show that job satisfaction can mediate the influence of organizational culture, compensation, and career development of the nurse's performance at X Hospital Denpasar. So expect the rules or system that is clearly linked to the organization's culture, compensation, and career development so the nurses' performance can be improved. Increasing the nurse's performance will have an impact on the optimal and sustainable service delivery to society.